Nurse Experience in Providing Holistic Care to Covid-19 Patients in Indonesia: A Qualitative Research - Siwi Ikaristi Maria Theresia; Eva Supriatin; Fransiska Anita Ekawati Rahayu Sa’pang; Serlina Sandi (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims: The study aimed to explore nurses’ experience in delivering holistic care among COVID-19 patients in designated care unit in Indonesian hospital. Methods: A qualitative study with phenomenology approach conducted. Population in this study were nurses from private and public hospital in West Java Province, Special Region of Yogyakarta and South Sulawesi. 10 participants recruited using purposive sampling with following inclusion criteria: taking care of COVID-19 patients and willingness to participate. Data collected through live interview, video calls and zoom meetings. Thematic data analysis was performed by understanding data or transcript results interview, composing codes and creating theme in accordance with the research purpose. Results: The study indicated 11 sub-themes and grouped into the three themes: 1) complains reported by COVID-19 patients, 2) Nurses’ intervention to fulfill physical, psychological, social and spiritual needs and 3) Nurses’ care as well as digital technology advantages as a means of therapeutic communication. The study discovered that nurses remain capable to fulfill needs of COVID-19 patients in a holistic approach. It includes the provision of physical, psychological, social and spiritual needs despite nurses experiencing inconvenient due to COVID -19 Personal Protective Equipment (PPE) standards. Conclusion: Holistic care is one mandatory consensus required to be carried out by nurses in taking care of COVID-19 patients as one interconnected bio - psycho - social- spiritual aspects. Holistic care for COVID-19 patients can take advantage of digital technology to fulfill it.